Ethanobotanical Survey of Plants in Bordi Region Used In Gastrointestinal and Urinary Track Infections - Mrs. Sarika Kale, Dr. Janhavi Ashish Arekar (International Journal of Innovative Research in Medical Science, 2017)
Bordi is small village in Dahanu Taluka, District Thane. The area under investigation is Aswali, Jambugaon, Khunawade, Gholwad and nearby padas which is a tribal area covered by thick dense forest, situated between 22052’ N latitude and 74020’ E longitude. The main ethnic tribes viz., Varli, Dhodi and Dubla are the largest tribal community residing in this area. All the three adivasi’s ethnic groups have strong belief on natural recourses for human welfare i. e. Panchamahabhuta. Aim of the research was to collect information of medicinal plant against different diseases. In present research efforts are made to collect the information of plants used in gastrointestinal and urinary track infection. The data collected during the numerous discussions with tribal people was recorded for further biological assay which supports the research work. Antimicrobial activity of all 15 plants was carried out on bacterial strains such as E. Coli, Salmonella paratyphi A, B. Subtilis and P. vulgaris.